Pengaruh Lingkungan Sekolah Terhadap Motivasi Belajar Siswa SMP N 3 Tarutung - Glorya Simanjuntak; Ruslan Juliana Pardosi; Robinhot Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of the school environment on the learning motivation of students at SMP Negeri 3 Tarutung in the 2025/2026 academic year. The method used in this research is an inferential quantitative research method. The population in this study consisted of all students of SMP Negeri 3 Tarutung in the 2025/2026 academic year, totaling 655 students. In this study, the sample size was determined to be 66 students using the stratified random sampling technique. Data were collected using a closed questionnaire consisting of 48 items. The results of the data analysis indicate that there is an influence of the school environment on students’ learning motivation at SMP Negeri 3 Tarutung amounting to 45.2%. These results can be proven through the research findings: (1) analysis prerequisite tests: (a) the normality test result = 0.54 > 0.05, indicating that the research data are normally distributed; (b) the linearity test = 0.132 > 0.05, indicating that there is a significant linear relationship between the two variables. (2) Hypothesis testing: (a) the correlation coefficient test obtained a value of rxy = 0.637 > 0.239, indicating that there is a positive relationship between variable X and variable Y; (b) the significance test of the correlation coefficient obtained a value of tcount = 7.270 > ttable = 1.669, indicating that there is a significant relationship between variable X and variable Y. Therefore, Ha is accepted and H0 is rejected. (3) The regression coefficient of determination test (r²) = 45.2%. Thus, the results of the study show that 45.2% of the school environment influences the learning motivation of students at SMP Negeri 3 Tarutung in the 2025/2026 academic year.